Mapping Twitter hate speech towards social and sexual minorities: a lexicon-based approach to semantic content analysis. Issue 7 (2nd July 2020) - Lingiardi, Vittorio; Carone, Nicola; Semeraro, Giovanni; Musto, Cataldo; D'Amico, Marilisa; Brena, Silvia
ABSTRACT: Though there are currently no statistics offering a global overview of online hate speech, both social networking platforms and organisations that combat hate speech have recognised that prevention strategies are needed to address this negative online phenomenon. While most cases of online hate speech target individuals on the basis of ethnicity and nationality, incitements to hatred on the basis of religion, class, gender and sexual orientation are increasing. This paper reports the findings of the 'Italian Hate Map' project, which used a lexicon-based method of semantic content analysis to extract 2, 659, 879 Tweets (from 879, 428 Twitter profiles) over a period of 7 months; 412, 716 of these Tweets contained negative terms directed at one of the six target groups. In the geolocalized Tweets, women were the most insulted group, having received 71, 006 hateful Tweets (60.4% of the negative geolocalized tweets), followed by immigrants (12, 281 tweets, 10.4%), gay and lesbian persons (12, 140 tweets, 10.3%), Muslims (7, 465 tweets, 6.4%), Jews (7, 465 tweets, 6.4%) and disabled persons (7, 230 tweets, 6.1%). The findings provide a real-time snapshot of community behaviours and attitudes against social, ethnic, sexual and gender minority groups that can be used to inform intolerance prevention campaigns on both local and national levels.